PERHITUNGAN AWAL IMBUHAN AIRTANAH ALAMI DAERAH ALIRAN SUNGAI CIKAPUNDUNG-GANDOK (KAJIAN PERBANDINGAN) - Al Hasyir, Muhammad Humaam; Soenarto, Bambang; Nurhayati, Yayah; Sembiring, Kristina; Tua Naibaho, Pio Ranap (JURNAL SUMBER DAYA AIR, 2024)
Groundwater recharge is a crucial factor in determining the permissible groundwater extraction within a watershed. In the Cikapundung watershed, the contribution of groundwater to raw water supply has been continuously declining, prompting a shift from groundwater to surface water usage. This study aims to quantify the groundwater recharge volume and recharge coefficient for each geological formation within the Cikapundung-Gandok watershed, covering an area of 90.4 km², and to compare the results with previous studies. The analysis estimates recharge volumes based on rainfall data from 8 stations around the Cikapundung-Gandok watershed from 2010 to 2019, geological formation data, and alternative recharge coefficients. The difference in recharge volume from previous studies is 393,348 m³/year or 1%. Two formations, Qvu and Qyu, which were not identified in earlier studies, supplement the existing geological dataset. The selected recharge volume for the Cikapundung-Gandok watershed is 33,232,004 m³/year or 1.05 m³/s, with the lowest contribution from the Lava formation (Qyl) at 1,364,504 m³/year or 0.04 m³/s and the highest from the Old Volcanic Product (Qvu) at 14,072,243 m³/year or 0.45 m³/s. The tentative recharge coefficients for each rock formation are as follows: Colluvium (Qc) 30%; Unweathered Old Volcanic Product (Qvu) 20%; Sand Tuff (Qyd) 10%; Lava (Qyl) 25%; Pumiceous Tuff (Qyt) 20%; and Young Volcanic Product (Qyu) 20%. The groundwater recharge data obtained can be used to set groundwater extraction limits and to plan for groundwater management using a conservative approach to ensure long-term sustainability.Keywords: groundwater recharge, recharge coefficient, geological formation, groundwater exploitation, Cikapundung-Gandok Watershed